Ionic Flexible Mechanical Sensors: Mechanisms, Structural Engineering, Applications, and Challenges - Ziqi Ren; Nishuang Liu; Qixiang Zhang; Jianyu Yin; Peixue Jia; Wenzhong Lu; Qianqian Yao; Mingfang Deng; Yihua Gao (Advanced Sensor Research, 2023)
Abstract This review covers the evolution of flexible mechanical sensors from an “electronic” language to an “ionic” language, which provides key reference information for the development of next‐generation bio‐intelligent sensing devices. Unlike sensors that rely solely on electron modulation, the core feature of the ionic flexible mechanical sensor (IFMS) is the ability of mechanical deformation to induce ion transport and compensation, thus demonstrating their conceptual similarity to biomechanical strain systems. Here, the basic design principles of flexible mechanical sensors modulated by ion transport are highlighted. This review provides a detailed description of the mechanotransduction mechanisms of IFMS devices based on ion transport modulation. First, although with similar mechanisms to conventional flexible mechanical sensors via piezoresistive, piezoelectric, and triboelectric transduction mechanisms, the core driver for IFMS devices is ions (not electrons). In addition, the transduction models and principles of action of novel transduction mechanisms that have been explored in the last decade are described in detail, which include interfacial iontronic sensing and potentiometric and electrokinetic energy conversion. According to the characteristics of the device, the relevant structural engineering is further highlighted. A comprehensive review of important IFMS application approaches (human–machine interfaces, life and health applications) is presented. Importantly, future challenges and possible solutions for IFMS devices are presented based on the existing research.